Theoretical and experimental simulation of roof-top bus multiple-circuit air-conditioning system performance - Mansour, M. Khamis; Musa, Md. Nor; Hassan, M. N. W.; Abdullah, H. (Professional Engineering Publishing, 2007)
Many air-conditioning (AC) systems are designed to operate at maximum cooling capacity regardless of the variation in the daily cooling load. At low loads, the conditions can be uncomfortably cold and the overcooling is an unnecessary waste of energy. To address these two issues, a multiple refrigeration circuit concept is proposed and applied to a roof-top bus AC system. A two-circuit model is proposed for a standard bus size in which each circuit has two evaporators of equal sizes arranged in parallel and installed on each passenger row, respectively. This means that each passenger row is served by two different evaporators sharing a common heat exchanger box. Depending on the cooling load, this concept allows one or both circuits (compressor motors) to be switched on and during either modes, it also allows one or more sets of evaporator blowers to be switched on. A steady-state computer model has been developed to simulate the performance of the proposed two-circuit AC system. A two-circuit air conditioner is also designed to form a roof-top bus AC system, fabricated, and installed on to an experimental rig. The experimental data are used to validate the computer model. The validation is on the system thermal performance and on the evaporator air outlet conditions (dry bulb temperature and relative humidity) at different modes of system operation, either at full or partial cooling loads. The simulated results gave satisfactory agreement with those obtained from the experimental work. Maximum absolute deviations are within the range of 19.3 per cent, although most of the simulated results are less than a 10 per cent range from the experimental ones, which validates the computer program. The paper describes the modelling work carried out and the results obtained are presented in comparison with the experimental data.